Avalia????o de tecnologias estat??sticas para servi??os de teleprote????o - Almeida, Luiz Felipe Fernandes de (2020)
Energy consumption has been growing continuously, being one of the main pillars of growth and economic development presented by today???s society. In this scenario, electric utilities provide the means to connect generating sources to final consumers. Systems such as teleprotection ones are used to ensure that faults in electrical networks do not affect consumers. Traditionally, energy utilities use Time-Division Multiplexing (TDM) technologies as a means of communication for teleprotection systems. However, their inefficient allocation of resources and their end of the life cycle make possible the use of new technologies, such as those ones based on IP (Internet Protocol). This work aims to evaluate the performance of statistical networks for the teleprotection service, with an emphasis on IP-MPLS technology and its variants, through proprietary solutions. The evaluation methodology used was based on the elaboration of test books and the realization of laboratory experiments with equipment used in the field by the energy utilities. The results of the tests show the potential feasibility of using statistical networks in relation to the operational requirements of teleprotection, constituting an important step for carrying out implementations in the field. Almeida, L. F. F. [masters dissertation]. Santa Rita do Sapuca????: Instituto Nacional de Telecomunica????es